Stable and radiogenic strontium isotope fractionation during hydrothermal seawater-basalt interaction. (1st November 2018) - Voigt, Martin; Pearce, Christopher R.; Baldermann, Andre; Oelkers, Eric H.
Abstract: The fluid-rock interactions occurring in hydrothermal systems at or near mid-oceanic ridges (MOR) were studied experimentally by reacting crystalline and glassy basalt with seawater at 250 °C and 290 °C while monitoring the liquid phase Sr isotopic evolution ( 87 Sr/ 86 Sr and δ 88/86 Sr). The results indicate that seawater Sr was incorporated into anhydrite during the early stages of seawater-basalt interaction. Liquid 87 Sr/ 86 Sr values trend towards the basaltic signature as non-stoichiometric basalt dissolution became the dominant process. This suggests that the interplay between fast Sr incorporation into secondary sulfates versus slow and continuous Sr liberation due to basalt dissolution at intermediate temperatures could partly explain previously identified discrepancies between MOR heat budget constraints and the marine 87 Sr/ 86 Sr budget. Late-stage anhydrite re-dissolution, likely caused by the liquid phase becoming more reducing through further basalt dissolution, as well as by quenching of the experiments, represents a potential explanation for the low amounts of anhydrite found in naturally altered oceanic basalt samples. Relatively strong decreases in liquid δ 88/86 Sr values in experiments with crystalline basalt suggest that isotopically light Sr was preferentially released due to non-stoichiometric dissolution. A slight preference of anhydrite for isotopically heavy Sr ( ε Anhydrite - Liquid 88 / 86 = 0.034 ± 0.019 ‰ ) is indicated by the data, suggesting that changes in MOR spreading rates and Sr removal could be recorded in the isotope compositions of authigenic, sedimentary Sr phases. Such insights will help to constrain the influence of hydrothermal systems on the oceanic stable Sr cycle.